The crime of maldevelopment: economic deregulation and violence in the Global South - Böhm, María Laura (Crimes of the powerful, 2019)
Introduction -- The Latin American economy, and the political and criminal-political context -- Visible and invisible violence according to Johan Galtung -- Seeing invisible violence : case studies from Mexico, Ecuador, Chile and Argentina -- Linking economy and visible violence : case studies from Guatemala, Brazil, Peru and Honduras -- The vicious circle of deregulated international businesses and violence -- The crime of maldevelopment as a needed conceptual category of criminology -- Approaching the crime of maldevelopment - conclusion and starting point